And how does that make you feel? eaudiobook Everything you (n)ever wanted to know about therapy. - Fletcher, Joshua (HarperAudio, 2024)
Psychotherapist Josh Fletcher takes us on a tour of the inner mind of a therapist—revealing a hilariously candid point of view on the therapeutic process, a practical guide to therapy, and maybe a few more cobwebs and dark corners than one might expect. It's everything you ever wanted to know about therapy (and maybe a few things you didn't). Trauma, heartbreak, anxiety, and mourning are all parts of the human experience, and Josh Fletcher's mission in life is to normalize the need to find a trusted professional with whom you can discuss all of life's scariest aspects. Through the lens of four of his patients—Daphne, a wildly successful actor who still struggles to find contentment; Levi, an intimidating bouncer with obsessive tendencies who's trapped in a sex cult; Zahra, an anxious, people-pleasing doctor in the midst of unpacking serious trauma; and Noah, a shy newcomer with some major closet skeletons—you'll share in their self-discovery and recovery as they untangle themselves from an all-too-familiar web of emotions. In between sessions, Fletcher struggles to balance his own well-being with that of his patients as details from his sometimes messy but always heartfelt personal life reveal that therapists aren't immune to getting tripped up by the same hurdles as the rest of us. And How Does That Make You Feel? is a primer on what to expect from therapy, how to find the right therapist, and the most common afflictions treated in therapy (such as depression, OCD, and panic attacks) as well as a darkly hilarious narrative about what's going on in your therapist's mind before, during, and after your session. Above all, it's filled with the promise that a better future is always possible . . . if we're willing to seek help and do the work.